Asymptotic statistical inference a basic course using R - Deshmukh, Shailaja; Kulkarni, Madhuri
The book presents the fundamental concepts from asymptotic statistical inference theory, elaborating on some basic large sample optimality properties of estimators and some test procedures. The book also discusses a score test and Wald’s test, their relationship with the likelihood ratio test and Karl Pearson’s chi-square test.